Teaching through Collective Trauma in the Era of COVID-19: Trauma-informed Practices for Middle Level Learners - Shantel D Crosby LMSW, PhD; Penny B Howell EdM, EdD; Shelley Thomas MAT, EdD (Middle Grades Review, 2020)
The COVID-19 pandemic has had an unprecedented impact on education and the ways in which teachers engage their students. Given the individual and collective traumatic nature and impact of this global health crisis, we provide specific strategies for addressing the needs of young adolescents while teaching remotely. Specifically, we posit that middle level educators should embed trauma-informed practices, focused on restoring safety and modeling adaptive behaviors, into their remote instructional practices. Recognizing that the COVID-19 crisis has a collective traumatic impact, affecting the lives and wellbeing of students and teachers alike, we also discuss the importance of self-care, providing strategies and resources for teaching professionals. Finally, we provide some guiding thoughts on how teachers might approach moving forward upon returning to face-to-face learning in the physical classroom.
Keywords: COVID-19; Childhood trauma; Collective trauma; Trauma-informed teaching; Self-care; pandemic pedagogy